Beta-Lactams : Novel Synthetic Pathways and Applications - Banik, Bimal K. (Springer International Publishing : Imprint: Springer, 2017)
This book presents an essential overview of beta-lactams and their medicinal value and use in the preparation of other biologically active compounds. Written by internationally respected authors, the individual chapters explore beta-lactams' synthesis, their mechanism of formation, biological effects, and function as base materials for other heterocycles of major importance.
Keywords: Chemistry.; Pharmacy.; Cancer research.; Drug resistance.; Organic chemistry.; Medicinal chemistry.; elektronické knihy; electronic books